ОДЗ: x >= -4 и x >= -3
=> x >= -3
замена: (чтобы коэффициенты поменьше были...) z = x+3
z+1 + 2*корень(2z(z+1)) + 2z = 49
2*корень(2z(z+1)) = 48 - 3z
4(2z^2 + 2z) = 48*48 - 6*48z + 9z^2
z^2 - (288+8)z + 2304 = 0
z^2 - 296z + 2304 = 0
D = 296*296 - 4*2304 = 87616 - 9216 = 78400 = 280*280
z1 = (296+280)/2 = 148+140 = 288
z2 = (296-280)/2 = 148-140 = 8
x1 = (z-3) = 288-3 = 285
x2 = (z-3) = 8-3 = 5
ПРОВЕРКА:
V289 + V576 = 17+24... посторонний (из-за возведения в квадрат...)
V9 + V16 = 3+4 = 7
ответ: х = 5
ответ: x=-3
Объяснение: 2x+3=x-5(x+3)
2x+3=x-5x-15 6x=-18 x=-3 проверка 2*-3+3=-3 -5(3-3) , -3=-3-0 => -3=-3
1) f'(x)= (4x³)'+(6x)'+3'= 12x²+6+0= 12x²+6
f''(x)= (12x²)'+6'= 24x+0= 24x
2) f'(x)= (7x³)'-(56x)'+8'= 21x²-56+0= 21x²-56
f''(x)= (21x²)'-56'= 42x-0= 42x